Tunisia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the analysis of the IMF's projections and estimates on Tunisia's basic data; sectoral distribution of GDP at constant and current prices; supply and use of resources at current and constant prices; consumer price index; balance of payments; selected exchange rate indices; revenue from the petroleum sector during 1995-2000; assets and liabilities of the central bank and deposit money banks; monetary survey; selected interest rates; direction of trade energy production and consumption during 1995-99; summary of the tax system; and so on.